2019
DOI: 10.1021/acs.jpcc.9b04280
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Nanostructures of Peptide Amphiphiles: Charge Regulation by Size Regulation

Abstract: Self-assembled nanostructures of peptide amphiphiles (PAs) with molecular structures C 16 K 2 and C 16 K 3 (where C indicates the number of carbon atoms in the alkyl chain and K is the lysine in the head group) were studied by a combination of theoretical modeling, transmission electron and atomic force microscopes, and acid−base titration experiments. The supramolecular morphology of the PAs (micelles, fibers, or lamellas) was dependent on the pH and ionic strength of the solution. Theoretical modeling was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(89 citation statements)
references
References 57 publications
6
83
0
Order By: Relevance
“…Short peptide amphiphiles (sPAs) or Lipid‐peptide conjugates exhibits a wide range of tightly packed self‐assembling nanostructures such as spherical micelles, vesicles, fibers and ribbons, etc [3,4,34–36] . These nanostructures demonstrate delicate balance between hydrophobicity from lipid alkyl chain and hydrophilicity from a group of peptide side chains [4,21–24,34] .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Short peptide amphiphiles (sPAs) or Lipid‐peptide conjugates exhibits a wide range of tightly packed self‐assembling nanostructures such as spherical micelles, vesicles, fibers and ribbons, etc [3,4,34–36] . These nanostructures demonstrate delicate balance between hydrophobicity from lipid alkyl chain and hydrophilicity from a group of peptide side chains [4,21–24,34] .…”
Section: Figurementioning
confidence: 99%
“…[31][32][33] Short peptide amphiphiles (sPAs) or Lipid-peptide conjugates exhibits a wide range of tightly packed self-assembling nanostructures such as spherical micelles, vesicles, fibers and ribbons, etc. [3,4,[34][35][36] These nanostructures demonstrate delicate balance between hydrophobicity from lipid alkyl chain and hydrophilicity from a group of peptide side chains. [4,[21][22][23][24]34] Such peptide coated gold nanoparticles can easily adopt amphiphilic nature of used sPA, hence facilitates stabilization and transportation of AuNPs through cell membranes.…”
mentioning
confidence: 99%
“…A selfassembly model of PAs produced by a C 16 alkyl tail linked to a chain of two lysines (C 16 K 2 ) or three lysines (C 16 K 3 ) stand reasonably accurate on the predicted behavior in terms of morphology, size and the state of protonation of the aggregates. The work by Zaldivar et al revealed that the system followed a charge regulation mechanism and found to decrease electrostatic repulsions between charged lysines (Zaldivar et al, 2019). An atomic level study by Rad-Malekshahi et al (2015a) analyzed the vesicle surface structure and dynamics of self-assembled nanovesicles along with the intermolecular forces between amphiphilic peptides to improve and tune the biophysical properties of the nanocarrier.…”
Section: Amphiphilic Peptidesmentioning
confidence: 99%
“…[1,4] As peptide sequences can be borrowed directly from natural proteins to create synthetic peptide amphiphiles, biomimetic functionality can be introduced into self-assembled nanostructures with defined morphologies facilitating the study of effects of local environment on peptide activity. [9,10] For example, peptide-lipid conjugates have generated assemblies capable of catalysis, [10,11] metal-binding, [12][13][14] stimuli-response, [15,16] and cell adhesion [17] while demonstrating the complimentary ways that electrostatics, polarity, hydrogen bonding, and sterics contribute to self-assembly. [18][19][20] Moving forward, building on this established knowledge base by adding new layers of complexity to the assembly landscape provides opportunities to bring peptide amphiphiles closer to the versatility and functionality of natural proteins.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] For example, peptide-lipid conjugates have generated assemblies capable of catalysis, [10,11] metal-binding, [12][13][14] stimuli-response, [15,16] and cell adhesion [17] while demonstrating the complimentary ways that electrostatics, polarity, hydrogen bonding, and sterics contribute to self-assembly. [18][19][20] Moving forward, building on this established knowledge base by adding new layers of complexity to the assembly landscape provides opportunities to bring peptide amphiphiles closer to the versatility and functionality of natural proteins.…”
Section: Introductionmentioning
confidence: 99%